Reduction on The Levels of Tannins from Stevia Rebaudiana Extract Using Activated Carbon - Triana Kusumaningsih; Nur Jannah Asrilya; Suci Wulandari; Dewi Restu Tri Wardani; Khoirul Fatihin (UNIVERSITAS SEBELAS MARET (UNS), 2015)
Extraction of tannins from leaves of Stevia rebaudiana using ethanol 30% with a temperature variation of 30, 50, 70 and 100oC for 3 hours was performed. Reduction on the levels of tannins in stevia extract is done by using activated carbon. The results showed the greatest weight of the extract at 70oC is 1.008 g and extract relatively alkaline pH. Reduction on the levels of tannins on stevia extracts done by passing the extract of stevia in the burette containing activated carbon as much as 4 times the cycle. Tannin concentration was reduced by 39.74%.